Human natural killing against ovarian carcinoma. - Shau, H. (Nature Publishing Group, 1983)
Natural killing (NK) by lymphocytes from normal individuals against primary and established ovarian carcinoma cell lines was tested in short-term chromium release assays. Two established cell lines and 5/6 primary cell lines tested showed significant susceptibility to NK. Primary cell lines are, in general, less sensitive to NK than long-term cultured target cells. A common NK recognition determinant on ovarian carcinoma cells and on the erythroleukaemic K562 cells was demonstrated by cold target inhibition assays. The recognition structure was also present on an ovarian cell line resistant to NK but not on the insensitive leukaemic cell line, SB. The activity against ovarian carcinoma cells was associated with the presence of large granular lymphocytes (LGL) previously shown to be the major effector cells against K562 targets. In fractions obtained by Percoll gradient centrifugation of lymphocytes, only fractions with a high content of LGL demonstrated good NK activity. LGL mediated NK against both non-adherent K562 and the adherent ovarian carcinoma target cells independent of monocytes.